The green chemistry of chalcones: Valuable sources of privileged core structures for drug discovery - Marotta, Ludovica; Rossi, Sara; Ibba, Roberta; Brogi, Simone; Calderone, Vincenzo; Butini, Stefania; Campiani, Giuseppe; Gemma, Sandra (Frontiers in Chemistry, 2022)
The sustainable use of resources is essential in all production areas, including pharmaceuticals. However, the aspect of sustainability needs to be taken into consideration not only in the production phase, but during the whole medicinal chemistry drug discovery trajectory. The continuous progress in the fields of green chemistry and the use of artificial intelligence (AI) are contributing to the speed and effectiveness of a more sustainable drug discovery pipeline. In this light, here we review the most recent sustainable and green synthetic approaches used for the preparation and derivatization of chalcones, an important class of privileged structures and building blocks used for the preparation of new biologically active compounds with a broad spectrum of potential therapeutic applications. The literature here reported has been retrieved from the SciFinder database using the term “chalcone” as a keyword and filtering the results applying the concept: “green chemistry”, and from the Reaxys database using the keywords “chalcone” and “green”. For both databases the time-frame was 2017-2022. References were manually selected based on relevance.